THE RELATIONSHIP BETWEEN ARTIFICIAL INTELLIGENCE AND PUBLIC SERVICE QUALITY: AN ANALYTICAL STUDY OF THE PUBLIC SECTOR IN THE KINGDOM OF SAUDI ARABIA - Amani Bani Alkahtani (Advances and Applications in Statistics, 2026)
This study aimed to examine the relationship between the use of Artificial Intelligence (AI) and the level of public service quality in the public sector of the Kingdom of Saudi Arabia. The study population comprised employees from five government entities that ranked among the top five in the 2024 Executive Report of the Digital Government Authority in terms of digital transformation compliance. These entities included the General Organization for Social Insurance (GOSI), the Ministry of Human Resources and Social Development (Ministry of HRSD), the Zakat, Tax and Customs Authority (ZATCA), the Saudi Data and Artificial Intelligence Authority (SDAIA), and the Ministry of Justice. The study adopted a descriptive survey approach. A structured questionnaire was distributed to a sample of 384 employees, of whom 327 responded, yielding a response rate of 85.2%. The study measured the impact of AI applications on multiple dimensions of public service quality, including reliability and operational accuracy, responsiveness and operational efficiency, citizen satisfaction and empathy in service delivery, decision support, job satisfaction and professional development, and integration with national platforms. The findings revealed that AI knowledge and experience among most public sector employees are concentrated at the basic and intermediate levels. More than half of respondents reported using AI tools daily or frequently, with a positive correlation observed between knowledge and experience levels and frequency of use. AI applications were primarily utilized in data analysis, decision support, and administrative process simplification, reflecting a governmental orientation toward leveraging AI to enhance operational efficiency and performance quality. Regarding perceived impact, most public sector employees indicated that AI use contributes positively to improving public service quality by accelerating task completion, reducing errors, enhancing operational efficiency, and improving decision-making quality. Based on these findings, the study recommends strengthening capacity-building, training, and professional development programs; advancing digital infrastructure; and fostering a culture of institutional innovation to maximize the benefits of AI technologies within the public sector.